Unraveling the immunological landscape and gut microbiome in sepsis: a comprehensive approach to diagnosis and prognosisResearch in context - Yali Luo; Jian Gao; Xinliang Su; Helian Li; Yingcen Li; Wenhao Qi; Xuling Han; Jingxuan Han; Yiran Zhao; Alin Zhang; Yan Zheng; Feng Qian; et al. (EBioMedicine)
Summary: Background: Comprehensive and in-depth research on the immunophenotype of septic patients remains limited, and effective biomarkers for the diagnosis and treatment of sepsis are urgently needed in clinical practice. Methods: Blood samples from 31 septic patients in the Intensive Care Unit (ICU), 25 non-septic ICU patients, and 18 healthy controls were analyzed using flow cytometry for deep immunophenotyping. Metagenomic sequencing was performed in 41 fecal samples, including 13 septic patients, 10 non-septic ICU patients, and 18 healthy controls. Immunophenotype shifts were evaluated using differential expression sliding window analysis, and random forest models were developed for sepsis diagnosis or prognosis prediction. Findings: Septic patients exhibited decreased proportions of natural killer (NK) cells and plasmacytoid dendritic cells (pDCs) in CD45+ leukocytes compared with non-septic ICU patients and healthy controls. These changes statistically mediated the association of Bacteroides salyersiae with sepsis, suggesting a potential underlying mechanism. A combined diagnostic model incorporating B.salyersia, NK cells in CD45+ leukocytes, and C-reactive protein (CRP) demonstrated high accuracy in distinguishing sepsis from non-sepsis (area under the receiver operating characteristic curve, AUC = 0.950, 95% CI: 0.811–1.000). Immunophenotyping and disease severity analysis identified an Acute Physiology and Chronic Health Evaluation (APACHE) II score threshold of 21, effectively distinguishing mild (n = 19) from severe (n = 12) sepsis. A prognostic model based on the proportion of total lymphocytes, Helper T (Th) 17 cells, CD4+ effector memory T (TEM) cells, and Th1 cells in CD45+ leukocytes achieved robust outcome prediction (AUC = 0.906, 95% CI: 0.732–1.000), with further accuracy improvement when combined with clinical scores (AUC = 0.938, 95% CI: 0.796–1.000). Interpretation: NK cell subsets within innate immunity exhibit significant diagnostic value for sepsis, particularly when combined with B. salyersiae and CRP. In addition, T cell phenotypes within adaptive immunity are correlated with sepsis severity and may serve as reliable prognostic markers. Funding: This project was supported by the National Key R&D Program of China (2023YFC2307600, 2021YFA1301000), Shanghai Municipal Science and Technology Major Project (2023SHZDZX02, 2017SHZDZX01), Shanghai Municipal Technology Standards Project (23DZ2202600).